Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 69. Beitrag. Coleoptera: Meloidae. - Kaszab, Zoltan (Contributions to Entomology = Beiträge zur Entomologie, 1967)
This paper sums up our present knowledge of the Meloidae of Albania. It covers the material collected by the expedition to Albania by Deutsches Entomologisches Institut (90 individuals of 12 species, 2 of them new finds), the collection made by Muraj in 1958 to 1960 (32 individuals of 10 species, including another 2 new finds) and so me separate finds made by Mader and other collectors from the Hungarian Museum of Natural History in Budapest, a total of 154 individuals of 17 species, 4 of them being new in the fauna of Albania. The results of the expedition made by Csiki in 1916 to 1918 (published in 1940), which was not strictly confined to the territory of the present People's Republic of Albania, were examined (and partly corrected) on the basis of the material in the museum in Budapest. Including the data given in previous publications, there are now 91 species of Meloidae established for the Balkan peninsula, but only 25 of these are at present known from AIbania.